Building Strong Banks Through Surveillance and Resolution - Enoch, Charles (International Monetary Fund, 2002)
Since the mid-1990s, economic observers have kept a watchful eye on the financial sector because of its potential to spark economic crises. Banks in particular have come under close scrutiny. This book offers guidance on setting up regulatory and supervisory regimes that can help to prevent crises, and on dealing with turmoil, should a crisis erupt. It contains a collection of essays on a wide range of issues useful to bolstering the banking and financial sector.